2017
DOI: 10.3390/ijms18112311
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of an Acetylcholinesterase Inhibitor, Donepezil, on Hippocampal Neuronal Death after Pilocarpine-Induced Seizure

Abstract: Epileptic seizures are short episodes of abnormal brain electrical activity. Many survivors of severe epilepsy display delayed neuronal death and permanent cognitive impairment. Donepezil is an acetylcholinesterase inhibitor and is an effective treatment agent for Alzheimer’s disease. However, the role of donepezil in seizure-induced hippocampal injury remains untested. Temporal lobe epilepsy (TLE) was induced by intraperitoneal injection of pilocarpine (25 mg/kg). Donepezil (2.5 mg/kg/day) was administered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It is well-established that neuronal death occurs in the brain after a seizure (Kim et al, 2012;Jeong et al, 2017;Lee S. H. et al, 2018), but the mechanisms through which this injury occurs remain elusive. When neuronal death occurs, an inflammatory response is initiated to restore tissue homeostasis and remove dead cells (Chapkin et al, 2009;Karin and Clevers, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well-established that neuronal death occurs in the brain after a seizure (Kim et al, 2012;Jeong et al, 2017;Lee S. H. et al, 2018), but the mechanisms through which this injury occurs remain elusive. When neuronal death occurs, an inflammatory response is initiated to restore tissue homeostasis and remove dead cells (Chapkin et al, 2009;Karin and Clevers, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Seizure is one of the most common neurological diseases, but methods for preventing the cell death mechanisms that occur post-seizure and repairing this injury after a seizure remain uncertain. Seizures cause serious damage to the hippocampus, and neuronal death is ultimately caused by a series of cell death cascades involving excessive inflammation, glial activation, apoptosis, oxidative stress, and zinc accumulation ( Kim et al, 2012 ; Jeong et al, 2017 ). Here, we focused on the rescue of seizure-induced neurological damage with cerebrolysin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effect of donepezil on spontaneous seizures was not examined, it was recently demonstrated that administration of donepezil following pilocarpine‐induced SE protected against hippocampal neuron loss . Furthermore, donepezil also protects against glutamate neurotoxicity .…”
Section: Introductionmentioning
confidence: 99%